Проектування металоабразивних притирів для чорнового доведення плоскопаралельних поверхонь - Сорочак, О. З. (Видавництво Національного університету «Львівська політехніка», 2001)
The mathematical model of flat surfaces forming at handling them on vibration development machine tools with circular trajectories of oscillations laps considered in this paper. The method of application of shape projection of the abrasive insertions metal-abrasive of instruments for a surfaces roughing of parts is designed on the basis of this model.